Analisis Persepsi Mahasiswa Fakultas Ilmu Komputer Terhadap Keamanan Sistem Infomasi Akademik Di Universitas Bhayangkara Jakarta Raya - Aziz Salim Adlianto; Daniel Kristiano Dali; Fadilah Zahra; Sheila Muhammad (Journal of Informatic and Information Security, 2024)
This research aims to analyze the perceptions of students at the Faculty ofComputer Science, Bhayangkara University, Greater Jakarta regarding the security ofthe academic information systems used. Academic information system security is acrucial aspect for protecting personal data, academic records and other importantinformation from potential security threats. Using a quantitative approach, data wascollected through a survey of a number of randomly selected students. The researchresults show that the majority of students have a positive perception of the security ofacademic information systems, although there are some concerns regarding potentialdata leaks and password security. Factors such as ease of use, system transparency, andthe system provider's efforts to provide education about security are the maindeterminants of student perceptions. It is hoped that these findings can provide input formanagers of academic information systems to improve their security and strengthenuser trust in the system.